(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article presents a comprehensive political analysis of the formation and development of the subsoil use mechanism in the context of environmental security in the Kyrgyz Republic based on the new edition of the Constitution of the Kyrgyz Republic (2021). The current issues of reform and other concepts that have been formed in Kyrgyzstan in the field of subsoil use, the accounting of which allows the evolutionary development of the Kyrgyz Republic, are also analyzed.